Ets1 and IL17RA cooperate to regulate autoimmune responses and skin immunity to Staphylococcus aureus - Battaglia, Michael; Sunshine, Alex C.; Luo, Wei; Jin, Richard; Stith, Alifa; Lindemann, Matt; Miller, Lloyd S.; Sinha, Satrajit; Wohlfert, Elizabeth; Garrett-Sinha, Lee Ann (Frontiers in Immunology, 2023)
Introduction Ets1 is a lymphoid-enriched transcription factor that regulates B- and Tcell functions in development and disease. Mice that lack Ets1 (Ets1 KO) develop spontaneous autoimmune disease with high levels of autoantibodies. Naïve CD4 + T cells isolated from Ets1 KO mice differentiate more readily to Th17 cells that secrete IL-17, a cytokine implicated in autoimmune disease pathogenesis. To determine if increased IL-17 production contributes to the development of autoimmunity in Ets1 KO mice, we crossed Ets1 KO mice to mice lacking the IL-17 receptor A subunit (IL17RA KO) to generate double knockout (DKO) mice. Methods In this study, the status of the immune system of DKO and control mice was assessed utilizing ELISA, ELISpot, immunofluorescent microscopy, and flow cytometric analysis of the spleen, lymph node, skin. The transcriptome of ventral neck skin was analyzed through RNA sequencing. S. aureus clearance kinetics in in exogenously infected mice was conducted using bioluminescent S. aureus and tracked using an IVIS imaging experimental scheme. Results We found that the absence of IL17RA signaling did not prevent or ameliorate the autoimmune phenotype of Ets1 KO mice but rather that DKO animals exhibited worse symptoms with striking increases in activated B cells and secreted autoantibodies. This was correlated with a prominent increase in the numbers of T follicular helper (Tfh) cells. In addition to the autoimmune phenotype, DKO mice also showed signs of immunodeficiency and developed spontaneous skin lesions colonized by Staphylococcus xylosus. When DKO mice were experimentally infected with Staphylococcus aureus, they were unable to clear the bacteria, suggesting a general immunodeficiency to staphylococcal species. γδ T cells are important for the control of skin staphylococcal infections. We found that mice lacking Ets1 have a complete deficiency of the γδ T-cell subset dendritic epidermal T cells (DETCs), which are involved in skin woundhealing responses, but normal numbers of other skin γδ T cells. To determine if loss of DETC combined with impaired IL-17 signaling might promote susceptibility to staph infection, we depleted DETC from IL17RA KO mice and found that the combined loss of DETC and impaired IL-17 signaling leads to an impaired clearance of the infection. Conclusions Our studies suggest that loss of IL-17 signaling can result in enhanced autoimmunity in Ets1 deficient autoimmune-prone mice. In addition, defects in wound healing, such as that caused by loss of DETC, can cooperate with impaired IL-17 responses to lead to increased susceptibility to skin staph infections.